Efektivitas Pembelajaran Daring Melalui Microsoft Sway Terhadap Hasil Belajar Kelas V SDN 1 Kacangan - Izzuddin Rifma Aji; Mira Azizah; Arfilia Wijayanti (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This research was conducted to determine the level of effectiveness of online learning through Microsoft Sway on learning outcomes for the Theme of 9 objects around us, Sub-theme of 2 objects in the economic activities of fifth grade students at SDN 1 Kacangan. The type of research used is quantitative. The population in the study were all fifth grade students at SDN 1 Kacangan, Blora Regency. The research method used is a pre-experimental design with a one-group pretest-posttest design. Data were obtained during the learning process and pre-test post-test. The results showed an increase in student learning outcomes V SDN 1 Kacangan. This is evidenced from the results of the hypothesis by using paired t-test with a level of 5%, namely T-count as much as 9.9456 and T-table as much as 2.0555, proving that T-count > T-table so that H0 is rejected and Ha is accepted. It can be concluded that there is an effectiveness of online learning through Microsoft Sway. Theme 9 Objects Around Us Sub-theme 2 Objects in Economic Activities on student learning outcomes in class V SDN 1 Kacangan.